Use of animation as a pedagogical tool to support science teaching (Research, Society and Development, 2023)
Education needs to be linked to what the student experiences, starting from the knowledge each student brings with them. Therefore, one of the challenges of Science Teaching is to make scientific theories understandable. In this way, the use of audiovisual resources can arouse interest in the subject. Based on the above, the present work aimed to analyze the potential of displaying animation in the process of teaching and learning science in the classroom. The study was carried out through research of a basic nature, through field research, with a qualiquantitative approach. First, a survey of scientific data was carried out, and later an experiment was performed through meetings, with expository and dialogued classes, carried out with three classes: two from the sixth year and one from the seventh year, from the second segment of Elementary School, from a school in the municipal network of the Rio de Janeiro city, totaling 106 participants. It was observed, in relation to the contents chosen to direct the research, a certain school disparity in the classes and a gap in the expected knowledge, with many of them presenting deficiencies in reading, interpreting texts, and writing, but it was possible to notice that the use of videos in the process of teaching and learning favored the interest and the understanding of the proposed themes, providing a better reception to the approached contents.